2021
DOI: 10.1039/d0nr08543j
|View full text |Cite
|
Sign up to set email alerts
|

Silver melamine thin film as a flexible platform for SERS analysis

Abstract: The new detection SERS platform is applicable for the quick and easy formation of sensing devices for food, agriculture, and environmental science. For quantitative sensing, it is important that a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This method typically involves in-situ chemical reduction of noble metal precursors physically dispersed in a flexible and adsorptive matrix, such as paper or textile. [109][110][111][112] For example, Ge, et al reported a large-scale synthesis of flexible cotton SERS wipes for trace analysis of surface residues. 113 The cotton SERS wipes were produced by dipping cotton sheets in AgNO 3 solution and then in a solution of ascorbic acid reducing agent, which led to the formation of Ag nanoparticles on the surface of the cotton fibers.…”
Section: In-situ Formation Of Plasmonic Nanoparticlesmentioning
confidence: 99%
“…This method typically involves in-situ chemical reduction of noble metal precursors physically dispersed in a flexible and adsorptive matrix, such as paper or textile. [109][110][111][112] For example, Ge, et al reported a large-scale synthesis of flexible cotton SERS wipes for trace analysis of surface residues. 113 The cotton SERS wipes were produced by dipping cotton sheets in AgNO 3 solution and then in a solution of ascorbic acid reducing agent, which led to the formation of Ag nanoparticles on the surface of the cotton fibers.…”
Section: In-situ Formation Of Plasmonic Nanoparticlesmentioning
confidence: 99%
“…Figure b shows the SERS spectra recorded using solutions containing 0.1–1000 ppm of Mel. The strong peak at 673 cm –1 is characteristic of the Mel molecule and can be observed in each spectrum (this peak is attributed to the ring-breathing II mode of Mel, which involves the in-plane deformation of the triazine ring) Figure c shows the variation of the intensities of the two main characteristic peaks of Mel (at 673 and 983 cm –1 ) plotted as a function of the concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The strong peak at 673 cm −1 is characteristic of the Mel molecule and can be observed in each spectrum (this peak is attributed to the ring-breathing II mode of Mel, which involves the in-plane deformation of the triazine ring). 42 Figure 6c shows the variation of the intensities of the two main characteristic peaks of Mel (at 673 and 983 cm −1 ) plotted as a function of the concentration. Note the use of logarithmic scales and excellent linearity of the intensity data (R 2 values of 0.993 and 0.986, respectively).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Films make it possible to grow nanostructures for SERS in situ. [ 72 ] Also, the application of the gradient structure formation based on the Liesegang rings formation process allows the formation of multifunctional complex films (Figure 5b). The ordered structure of silver nanoparticles in a film of agarose and pectin demonstrates a selective response to benzenethiol, which is a calibration standard for the determination of pesticides (Figure 5c).…”
Section: Freestanding Filmsmentioning
confidence: 99%
“…The ordered structure of silver nanoparticles in a film of agarose and pectin demonstrates a selective response to benzenethiol, which is a calibration standard for the determination of pesticides (Figure 5c). [ 72 ]…”
Section: Freestanding Filmsmentioning
confidence: 99%